La bioética aplicada en la gestión de enfermería en el Hospital General Machala. - Romero Chuquimarca, Johanna Estefanía (My University, 2025)
Abstract: Bioethics is a fundamental pillar in nursing care management, especially in highly demanding clinical settings such as the emergency department. This research aimed to determine the application of bioethical principles by nursing staff at Machala General Hospital, assessing their level of knowledge, perception, practical application, and perceived institutional barriers. A quantitative, descriptive, cross-sectional study was conducted with a sample of 42 nursing graduates. A structured Likert-type questionnaire was used, validated by experts and with a Cronbach's alpha of 0.94. The instrument addressed four key dimensions: knowledge, perception, application, and ethical barriers. The results showed that 90% of staff reported being familiar with bioethical principles, and 93% recognized their applicability in clinical management. However, only 52% had received formal training in bioethics. Promoting well-being was the most valued dimension (95%), while participatory resolution of ethical conflicts received less consensus (67%). The most frequent dilemas included prioritization of patients (74%), unequal workloads (69%), and lack of institutional support (61%). It was concluded that, although staff demonstrate a solid ethical foundation, structural barriers persist that limit its effective application. It is recommended that continuing education be strengthened, healthcare ethics committees be created, and policies be established that promote a bioethical and participatory institutional culture.
Resumen: La bioética constituye un eje fundamental en la gestión del cuidado enfermero, especialmente en contextos clínicos de alta exigencia como el área de emergencia. Esta investigación tuvo como objetivo determinar la aplicación de los principios bioéticos por parte del personal de enfermería del Hospital General Machala, evaluando su nivel de conocimiento, percepción, aplicación práctica y las barreras institucionales percibidas. Se desarrolló un estudio cuantitativo, descriptivo, de corte transversal, con una muestra de 42 licenciados/as en enfermería. Se utilizó un cuestionario estructurado tipo Likert, validado por expertos y con un alfa de Cronbach de 0.94. El instrumento abordó cuatro dimensiones clave: conocimiento, percepción, aplicación y barreras éticas. Los resultados mostraron que el 90 % del personal afirmó conocer los principios bioéticos, y el 93 % reconoció su aplicabilidad en la gestión clínica. Sin embargo, solo el 52 % había recibido formación formal en bioética. La promoción del bienestar fue la dimensión más valorada (95 %), mientras que la resolución participativa de conflictos éticos registró menor consenso (67 %). Los dilemas más frecuentes incluyeron la priorización de pacientes (74 %), cargas laborales desiguales (69 %) y falta de apoyo institucional (61 %). Se concluye que, aunque el personal demuestra una sólida base ética, persisten barreras estructurales que limitan su aplicación efectiva. Se recomienda fortalecer la formación continua, crear comités de ética asistencial y establecer políticas que promuevan una cultura institucional bioética y participativa.
Keywords: BIOÉTICA; ENFERMERÍA; GESTIÓN DEL CUIDADO; ÉTICA CLÍNICA